Brand teams and the brand management structure in pharmaceutical and other fast-moving consumer goods companies - Veloutsou, Cleopatra A.; Panigyrakis, George G. (My University, 2001)
In the modern business environment, team building and the development of relationships with the various interfaces for the benefit of their brands are very important activities for brand managers. This study examines an extending organizational phenomenon, namely the development of teams for effective brand management in various local markets. In particular, it investigates the way brand managers in the fast moving consumer goods and pharmaceutical industries comprehend team roles and activities by analysing the allocation of their working time and the perceived contact and significance of relationships with their interfaces. Based on the product management literature, the structure of the local brand’s team was empirically examined using data collected from a sample of 187 product managers working for 58 companies in different sectors in Greece. The results show that four subgroups were developed in the various sectors, but with different members. © 2001 Taylor & Francis Ltd.
Keywords: Brand management; Greece; Marketing organization; Pharmaceutical industry; Teams